Indonesian university teachers' views on their autonomy in using Moodle for English language teaching - Werdiningsih, Indah; Yazid Basthomi; Mukminatien, Nur; Yannuar, Nurenzia (Issues in educational research, 2025)
The ubiquity of Moodle and similar learning management systems has transformed education, offering opportunities for personalised and adaptive learning. Moodle enables teachers to customise instructional materials and methods to meet diverse student needs. Despite its potential, limited research has explored how teachers use Moodle to exercise autonomy in teaching. This study investigates how teachers utilise Moodle, a well-known learning management system, to practice autonomy in contemporary education. Using a case study approach, we examine eight teachers and the English courses they teach at a university in East Java, Indonesia. Data were collected through a Moodle analytic framework to analyse usage patterns, and open-ended questionnaires to capture teachers' experiences. Thematic analysis revealed that teachers use Moodle to customise resources, create interactive lessons, design collaborative activities, and implement flexible assessments. Teachers valued the flexibility offered by Moodle, which enabled diverse teaching strategies and personalised learning. However, challenges such as technological issues and restrictive institutional policies hindered its full potential. Our research highlights the role of Moodle in fostering teacher autonomy while emphasising the need for technical training and professional development to address barriers. By overcoming these challenges, teachers can better utilise Moodle to support innovative, student-centred learning.